Perceived cognitive impairment in high school students in the United States - Iverson, Grant L.; Iverson, Ila A. (Frontiers in Psychology, 2022)
Introduction: Some youth experience cognitive difficulties that interfere with their ability to learn and function well in a school environment. We examined correlates of perceived cognitive impairment among high school students who completed a national survey conducted by the United States Centers for Disease Control and Prevention (CDC) in 2019. Methods: Participants were high school students (grades 9-12) who completed the Youth Risk Behavior Survey (YRBS) in 2019. The CDC uses this survey to monitor risk behaviors. Students answered the following question ‘Because of a physical, mental, or emotional problem, do you have serious difficulty concentrating, remembering, or making decisions?’ as either ‘yes’ or ‘no.’ Student responses to this question were analyzed in relation to demographic variables and variables pertaining to adversity, mental health problems, and drug use. Results: The sample included 8,349 students between the ages of 14 and 18, with 4,093 boys (49%) and 4,256 girls (51%). A large proportion reported having serious difficulty concentrating, remembering, or making decisions due to physical, mental, or emotional problems (38%). A significantly larger proportion of girls (45%) than boys (30%) reported experiencing cognitive impairment [χ2(1)=212.23, p<.001; Odds Ratio=1.95, 95% confidence interval=1.78-2.13]. Youth who exercised regularly were significantly less likely to report cognitive impairment. Binary logistic regression was used to examine the associations between perceived cognitive impairment and adversity, mental health, and lifestyle variables separately for boys [χ2(11)=569.158, p<.001; Nagelkerke R2=.212] and girls [χ2(11)=1,026.189, p<.001; Nagelkerke R2=.321]. Being bullied, feeling unsafe or threatened at school, getting very low grades, insufficient sleep, and using illicit drugs were independently associated with perceived cognitive impairment in both boys and girls—after controlling for associations with depression and suicidality. Youth who denied mental health problems, psychosocial adversities, and using illicit drugs reported much lower rates of perceived cognitive impairment (boys=13%, girls=15%). Conclusions: A remarkably large proportion of high school students in the United States reported experiencing serious difficulty with their cognitive functioning over the past year. Girls were significantly more likely to endorse perceived cognitive difficulties compared to boys. There was a strong association between perceived cognitive impairment and the experience of psychosocial adversity.